Gastrointestinal changes in paediatric malnutrition that may impact on nutrition choice - Meyer, Rosan; Arpe, Lauren; Kansu, Aydan; Kelly, Veronica; Lindley, Keith; O'Meara, Mairéad; del Carmen Rivero, Maria; van Zundert, Suzanne; Vicente-Santamaría, Saioa; Žaja, Orjena; Oliveros, Elena; Olivier, Leanne; et al. (Frontiers in Pediatrics, 2025)
Undernutrition is defined as “a condition resulting from imbalanced nutrition or abnormal utilization of nutrients.” In this paper, the term malnutrition is used to refer to undernutrition. Malnutrition may be driven by poor socioeconomic conditions or by disease, and it is estimated that disease-related malnutrition (DRM) impacts up to 28% of hospitalized children in Europe. Malnutrition results in alterations in gastrointestinal function that lead to malabsorption of macro- and micro-nutrients. It can lead to altered gut motility and a deficiency of stomach acid, which can result in intestinal colonization by pathogens, causing diarrhoea and high burdens of intestinal infection. The presence of compromised gastrointestinal function in children with DRM is critical as it negatively impacts the efficacy of nutritional support and recovery. When choosing novel strategies and nutritional therapies for malnourished children, consideration should be given to gut-protective interventions that promote better treatment tolerance. When breastmilk is unavailable, whole protein feeds are currently considered as first-line treatment for malnutrition in children with a normal functioning gastrointestinal tract. However, peptide-based feeds have been associated with improved gastrointestinal tolerance and absorption, reduced diarrhoea, reduced inflammation, improved growth and have restored gut integrity compared with free amino acid and whole-protein feeds. At a recent meeting, experts in this area have identified significant research gaps in the literature on peptide-based feeds in children and possible gaps in clinical practice. Whilst the group acknowledges that further work is needed, this paper provides an overview on this topic to further drive research in this area.